Geneflow 2002 - Cherfas, J.; International Plant Genetic Resources Institute (2002)
This is a publication that serves to contribute to the flow of information about the importance of the Earth's plant genetic resources. This issue focuses on genebanks: their future is our future, plus news of how plants are being used to drive development and fight poverty